A novel and efficient route to azabicycles via the isocyanate-mediated twofold cyclization. Issue 11 (17th March 2016) - Li, Mingming; Xing, Ping; Jiang, Biao
Abstract: A new one-pot route to azabicycles involving the [3, 3]-sigmatropic rearrangement of dehydration product from allylic alcohol carbamate and base promoted twofold cyclization was described. Graphical abstract: